The paradoxes of aesthetic emotion: from horror to promise (2014)
Works of art have the power toevoke the paradox of a time and aspace prior to existence. This concernsthe subject itself and its desireto advance toward the unknownthrough aesthetics as a quality ofits feeling. Aesthetic emotion isaddressed here in its function ofindicating the reality of drives andpointing to that which cannot bethought, that is, the unconscious.The article explores how aestheticfeeling can pave the way to subvertdrives and open it up to anotherfacet of existence, suggesting thataesthetic emotion serves an essentialfunction in dealing with horrorand clinging to the human, as wellas to the promise of a possible life.In this sense, the path involves anethical commitment.